Effects of Cd addition on soil phosphorus mineralization in reclaimed coastal wetlands along a 100-year reclamation chronosequence in the Pearl River Estuary (China) - Liu, Zhe; Gao, Zhaoqin; Bai, Junhong; Zhang, Guangliang; Tang, Ruoxuan; Chen, Guozhu (Frontiers in Marine Science, 2022)
The relationship between Cd and soil phosphatase activity has been given some concerns due to serious soil Cd contamination. However, the effects of high-risk Cd pollution on the soil phosphorus mineralization process are still kept unclear in reclaimed coastal wetlands. Here, we investigated the impacts of Cd additions at three levels on phosphorus mineralization and phosphatase activities in reclaimed coastal wetland soils with different reclamation ages (e.g., 100-year, 40-year, and 10-year) in the Pearl River Estuary by a 40-day laboratory incubation experiment. The results showed that lower soil phosphatase activity was observed in the reclaimed wetlands with longer reclamation age, which led to the lower increase in cumulative net phosphorus mineralization and Occluded P. High Cd exposure facilitated the phosphatase activities and phosphorus mineralization through the promotion of Occluded P and Al/Fe-P contents in the 100-year and 10-year reclaimed wetland soils, respectively. The addition of the low-dose of Cd to the soil inhibited phosphorus mineralization in the middle of incubation in 40-year reclaimed wetland soils, while the high-dose Cd addition had little effect. The findings of this work indicate that the older reclaimed wetlands might have lower phosphorus mineralization potentials, while higher Cd pollution might lead to soil phosphorus loss by improving phosphorus mineralization in reclaimed coastal wetlands.